2014
DOI: 10.1080/17441692.2014.891631
|View full text |Cite
|
Sign up to set email alerts
|

Income-based disparities in health care utilisation under universal health coverage in Brazil, 2002–2003

Abstract: Since Brazil's adoption of universal health care in 1988, the country's health care system has consisted of a mix of private providers and free public providers. We test whether income-based disparities in medical visits and medications remain in Brazil despite universal coverage using a nationally representative sample of over 48,000 households. Additional income is associated with less public sector utilisation and more private sector utilisation, both using simple correlations and regressions controlling fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…However, this literature also points to an increase in perceived barriers to access, often related to changes in people’s expectations and overcrowding of facilities due to a growing demand for services. In terms of equity, studies have shown that individuals with less income and education and without formal employment are more likely to face barriers to care, and present lower levels of utilization, after controlling for age and health status, than their counterparts [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…However, this literature also points to an increase in perceived barriers to access, often related to changes in people’s expectations and overcrowding of facilities due to a growing demand for services. In terms of equity, studies have shown that individuals with less income and education and without formal employment are more likely to face barriers to care, and present lower levels of utilization, after controlling for age and health status, than their counterparts [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…[30] This has led to an increase in patient cost-sharing (e.g., out-ofpocket expenditures) for persons in the lower economic strata, as well as nearly 400,000 lawsuits related to insu cient health coverage. [50]. Two studies found that out-of-pocket health spending was higher in the groups covered by this program, even when compared to higher-income populations with private medical insurance.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies found that out-of-pocket health spending was higher in the groups covered by this program, even when compared to higher-income populations with private medical insurance. [50] Colombia has also been plagued by underfunding of its subsidized POS component, as well as high rates of informal workers evading their health contributions. Insu cient funding has furthered health inequities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1988, the country introduced a public and comprehensive Unified Health System (UHS, denominated SUS in Portuguese), with emphasis on primary care on the community level, whose main pillar is the Family Health Strategy (FHS). It is executed by means of a multidisciplinary health team assisting a circumscribed population employing prevention approaches [ 15 ], professional appointments for spontaneous demands [ 16 ] and longitudinal follow-up and treatment of chronic diseases [ 17 ] including periodontal disease [ 18 ].…”
Section: Introductionmentioning
confidence: 99%